The Effect of Human Resources, Financial Literacy, Financial Management, and Access to Capital on MSME Financial Performance - Bakri Soamole; Mohammad Khotib; Asri Thalib; Arman Ali (Research Horizon, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are crucial for economic growth and employment, yet many in North Ternate District face challenges such as limited resources, uneven managerial skills, and restricted access to capital, making competency development essential for sustainable financial performance. This study examines the key factors influencing MSME financial performance, including human resources, financial literacy, financial management, and access to capital. Data were collected using a quantitative approach from 88 MSME actors through structured questionnaires and analyzed using multiple linear regression with SPSS version 27. The results show that human resource capability does not have a significant impact on financial performance, while financial literacy, effective financial management, and access to capital positively and significantly contribute to improving financial outcomes. The findings provide practical implications for policymakers and MSME practitioners. By strengthening financial literacy programs, promoting sound financial management practices, and facilitating easier access to capital, stakeholders can support the sustainable growth of MSMEs. This study also contributes to the academic literature by highlighting the critical factors beyond human resources that drive MSME success and offering actionable insights for regional economic development.